Business Environment and Entrepreneurial Motivations of Urban Students - Wu, Feixia; Mao, Chuanyu (Frontiers in Psychology, 2020)
The entrepreneurial environment is quite crucial for the undergraduates to consider their entrepreneurial motivation. With the domestic promotion of mass entrepreneurship and innovation, there are more undergraduates tend to create their own business. However, the differences of the urban entrepreneurial environment have resulted in the extremes of “cluster" or "outflow" in urban undergraduate entrepreneurship, which brings an adverse impact to economic development. This paper studies the 244 undergraduates in Wenzhou city, and analyzes the relationship between the urban entrepreneurial?environment and the undergraduates' entrepreneurial motivation, on this basis, it tests the hypotheses and draws out some conclusions: the factors of economic foundation, educational training, financial support and non-financial support, which have a significant positive impact on undergraduates' entrepreneurial motivation, while the regulating effect of government policies?is?in-apparent.